2010
DOI: 10.4314/ajtcam.v6i4.57194
|View full text |Cite
|
Sign up to set email alerts
|

Protection of swimming-induced oxidative stress in some vital organs by the treatment of composite extract of <i>Withania somnifera, Ocimum sanctum</i> and <i>Zingiber officinalis</i> in male rat

Abstract: Composite methanolic extract of roots of Withania somnifera, leaves of Ocimum sanctum, and rhizomes of Zingiber officinalis was administered by gavage at the dose of 40 mg 100 g −1 body weight day −1 to rat orally for 15 days prior to experimentation followed by co-administration of above extract at the same dose for 28 days of swimming to find out the remedial effect of this extract on exhaustive physical exercise-induced oxidative damage. Swimming resulted significant diminution (p<0.05) in the activities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Malondialdehyde (MDA) has been the most widely used parameter for evaluating oxidative damage to lipids, although, it is known that oxidative damage to amino acids, proteins and DNA also causes release of MDA. Previous studies had indicated that exhaustive exercise causes an increase in MDA and the MDA increasing due to excess oxygen radical reacting polyunsaturated acid in the muscle (Misra et al, 2009;Sun et al, 2010). The present study demonstrated that the GPMP supplementation can promote increases in the activities of these antioxidant enzymes (SOD, GPH-Px and CAT) and reduce lipid peroxidation.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Malondialdehyde (MDA) has been the most widely used parameter for evaluating oxidative damage to lipids, although, it is known that oxidative damage to amino acids, proteins and DNA also causes release of MDA. Previous studies had indicated that exhaustive exercise causes an increase in MDA and the MDA increasing due to excess oxygen radical reacting polyunsaturated acid in the muscle (Misra et al, 2009;Sun et al, 2010). The present study demonstrated that the GPMP supplementation can promote increases in the activities of these antioxidant enzymes (SOD, GPH-Px and CAT) and reduce lipid peroxidation.…”
Section: Discussionsupporting
confidence: 67%
“…It is known that antioxidant enzymes exhibit synergistic interactions by protecting each other from specific free radical attacks (Perse et al, 2009). The significant decrease in the activities of SOD, GPH-Px and CAT in the muscle tissue after forced swimming may be an indication of exercise-induced oxidative threat (Misra et al, 2009). Malondialdehyde (MDA) has been the most widely used parameter for evaluating oxidative damage to lipids, although, it is known that oxidative damage to amino acids, proteins and DNA also causes release of MDA.…”
Section: Discussionmentioning
confidence: 99%
“…After the final treatment with POP, the mice were taken out for the forced swimming exercise. The procedure used was described previously with some modifications [12]. Briefly, the mice were dropped individually into an acrylic plastic pool (50 cm × 50 cm × 40 cm) filled with fresh water maintained at 25 ± 2 °C, approximately 30 cm deep so that mice could not support themselves by touching the bottom with their tails.…”
Section: Swimming Exercise Testmentioning
confidence: 99%
“…Exhaustive swimming was selected as a model of physical exercise since muscle trauma caused by other types of physical exercise, including prolonged running on a treadmill, exercise stimulated by electric shock and plyometric contractions, may be avoided (20,21). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%